The growth of the American economy - Williamson, Harold Francis (New York : Prentice-Hall, 1951)
The original chapters were carefully checked by their respective authors and rewritten in part or in whole wherever more recent scholarship gave a clearer understanding of the subject matter. Two chapters covering the important subject of marketing have been added to the topics treated in the first edition. In this edition, the first period ends with 1789, the second with 1865, the third with 1918, and the last with 1950. The arrangement makes it possible to give better perspective to developments since World War 1.
Includes bibliographical references and index.
rpm 06/06/2017
Loans
Keywords: American Economy; United States